Financial Literacy and Saving Attitude among Malaysian Population - Ng, Kar En; Ang, Sin Lin; Armaan Singh, Harban Singh; Chain, Mee Kee; Lim, Qiao Ying; Wang, Chong; Gong, Peihao (INTI International University, 2024)
This research was designed to determine whether age, gender, and ethnicity have a significant effect on the saving attitude. This study aims to assess the financial literacy of Malaysian adults and identify their wealth-accumulation habits as a precondition for their retirement planning decisionmaking. It creates a framework based on financial capabilities, availability, accessibility, and affordability of private retirement plans, as well as individuals' awareness of these requirements. The findings will help policymakers encourage private retirement planning and the industry create retirement packages that appeal to a wider range of people. All participants were notified that their involvement was optional, and their responses would be kept confidential. The aim of the sampling method was to acquire a representative sample of the population through random selection. Based on all these findings, it will enable policymakers to incentivize private retirement planning and help the industry develop retirement packages.